2015
DOI: 10.1179/1743281215y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of electromagnetic field and flow field in round billet continuous casting mould with electromagnetic stirring

Abstract: A three-dimensional mathematical model of mould electromagnetic stirring (M-EMS) was established. Based on Maxwell's equations, the continuity equation and the momentum equation, the distribution characteristics of electromagnetic and flow fields with M-EMS were numerically simulated by the finite element software ANSYS and the finite volume software CFX. The influence of M-EMS on electromagnetic and flow fields was examined, and the process parameters of M-EMS were optimised by industrial plant trials. By the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Yu and Zhu [12] numerically simulated the effect of operation parameters of M-EMS on the magnetic field, temperature profile, and inclusion trajectories in a round billet continuous casting mold, and carried out the industrial trials to study the effect of M-EMS parameters on the solidification structure and macrosegregation in continuously cast bloom of high carbon steel. Geng et al [13] performed numerical simulations to optimize the M-EMS parameters using a 3D mathematical model and finally determined the optimal M-EMS parameters for the round billet continuous casting by industrial trials.…”
Section: Introductionmentioning
confidence: 99%
“…Yu and Zhu [12] numerically simulated the effect of operation parameters of M-EMS on the magnetic field, temperature profile, and inclusion trajectories in a round billet continuous casting mold, and carried out the industrial trials to study the effect of M-EMS parameters on the solidification structure and macrosegregation in continuously cast bloom of high carbon steel. Geng et al [13] performed numerical simulations to optimize the M-EMS parameters using a 3D mathematical model and finally determined the optimal M-EMS parameters for the round billet continuous casting by industrial trials.…”
Section: Introductionmentioning
confidence: 99%
“…At present, in-mold electromagnetic stirring (M-EMS) used to optimize molten steel flow is a widely accepted technique in big bloom casting, which has been proved to be beneficial to enhance the columnar-to-equiaxed transition during solidification and reduce the surface and subsurface defects [1][2][3]. Geng et al [4] and Yu et al [5] indicated that the EMS parameters affects the metallurgical behavior and the steel quality significantly, an optimum EMS parameter for a certain bloom should be proposed for a higher quality. Recently, numerous mathematical and experimental studies on the CC process involving M-EMS were conducted to investigate the flow field distribution of molten steel [6][7][8][9], and the heat transfer and initial solidification behaviors influenced by EMS induced fluid flow were also studied in past years [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…* The effect of melt flow on electromagnetic field was ignored due to the small magnetic Reynolds number (about 0.01) in stirring region, and electromagnetic field was assumed to be in quiescent state [10]. The electromagnetic force was obtained in a timely averaged form, * The influence of Joule heating generated by the induced current was ignored in the computation of heat transfer [9,10], * The iron core of stirrer was assumed to be magnetically linear with a constant permeability [10]. The cooling water jacket of the CC mould, the stainless steel protective jacket of the EMS and other insulation material in the EMS device were all simplified as paramagnet in this study.…”
Section: Model Description 21 Basic Assumptionsmentioning
confidence: 99%
“…Much work on the metallurgical effects of the M-EMS has been carried out by scholars in recent years. An et al [8] and Geng et al [9] numerically and experimentally investigated the melt flow, heat transfer, and inclusion trajectory in the round casting with M-EMS, and shown that the strand central porosity can be improved obviously under the optimum stirring parameters of M-EMS. Trindade et al [10] presented coupled models to study the turbulent flow and solidification behaviors during the CC process, and indicate that the M-EMS can improve superheat dissipation, prevent the superheated jet moving downward and weaken the invasion depth of the jet.…”
Section: Introductionmentioning
confidence: 99%